Karakteristik Perkembangan Masa Dewasa Awal: Karakteristik Perkembangan Masa Dewasa Awal - Frezy Paputungan (LPPM UNiversitas Bina Mandiri Gorontalo, 2023)
Adult age is very interesting to study, firstly because it enters the longest age in the stages of human life, secondly, undergoing heavy and complex developmental tasks with various dynamics of physical and psychological problems as a result of previous developments, third, mature age in solving challenges life, fourth, How does the concept of Islam view adulthood. The purpose of this article is to add Knowledge of how each individual is able to deal with and enter adulthood, both early, middle and late adulthood. Able to prepare physically and psychologically healthy which will have a positive impact on oneself and the environment. The research method of this article is qualitative, using in-depth interviews, observation and documentation approaches. Adulthood is the initial and difficult time for an individual in adjusting himself to a new life and new social expectations. At this time, an individual is required to let go of dependence on parents and try to be independent as an adult human being. Adult development becomes an age of extraordinary challenges throughout the life span and varies according to times and cultures (Berry, Poortinga, Segall, 1999). The problems experienced by adults include being unable to pass through the stages Its development is well marked by the many problems faced when entering adulthood starting with problems of losing self-identity, being anti-social, failing to settle down, not being able to be a good model for their children, not being able to support their family, etc.